The Tuskegee airmen - Brooks, Philip (Minneapolis, Minn. Compass Point Books, 2005)
Takes a look at the African Americans who served as aviators in World War II.
Dark days -- Fighting to fly -- Learning to be pilots -- Freedom fliers -- Partial victory -- Tuskegee institute -- Ready and waiting -- Finally getting their chance -- Glossary -- Did you know? -- Important dates -- Important people -- Want to know more? -- Index.
Includes bibliography references and Index
1050L
Keywords: United States, Army Air Forces -- Fighter Group, 332nd -- Juvenile literature -- History; World War -- Participation, African American -- Juvenile literature -- 1939-1945; World War -- Aerial Operations, American -- Juvenile literature -- 1939-1945; African Americans -- Juvenile literature; African American air pilots -- Juvenile literature; Tuskegee Army Air Field (Ala.) -- Juvenile literature; African American air pilots; World War -- African Americans -- 1939-1945; World War -- Aerial operations -- 1939-1945; African Americans; African American air pilots